Diversification of body shape in Sebastes rockfishes of the north‐east Pacific. (18th August 2015) - Ingram, Travis
<x xml:space="preserve">Abstract</x> Body shape variation is integrally related to many aspects of fish ecology, including locomotion and foraging, and can indicate the functional diversity of fish assemblages. Few studies have thoroughly characterized body shape in a diverse marine fish clade, or investigated both temporal and spatial patterns of variation in body shape disparity. Here, I use digital photographs to measure geometric body shape in 66 species of north‐east Pacific rockfish (Sebastes spp.), including a correction for error introduced by arching of specimens. Different components of interspecific shape variation show associations with fish size, depth habitat, trophic niche and phylogenetic relationships. Overall, the accumulation of body shape disparity appears to have been near‐constant over time, and shows little variation across the latitudinal range of rockfish.